FORMULATION AND EFFICACY TEST OF STICK-HEEL MOISTURIZER MADE FROM 96% ETHANOL EXTRACT OF PAPAYA (Carica papaya L.) LEAVES - Marangyana, I Gede Bagus Indra; Listiani, Putu Ayu Ratih (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2025)
Papaya leaves contain phytochemicals including alkaloids, phenols, flavonoids, tannins, saponins, and steroids, which can function as natural moisturizers to maintain healthy heels. Papaya leaves were extracted using the maceration method with 96% ethanol solvent and evaporated on a rotary evaporator to obtain a thick extract. The yield was 10.2%. It was subsequently combined at concentrations of 5 %, 10 %, and 15% to create a moisturizing heel stick preparation. The physical quality of the stick heel moisturizer preparations was assessed using tests for homogeneity, spreadability, adhesion, pH, organoleptic properties, and moisturizing properties. The mixture produces a brownish-green stick, a semi-solid texture, a distinctive odor of papaya leaves, a pH of 6, good homogeneity, good adherence, and qualified spreadability. The moisturizing test results for FI 5%, FII 10%, and FIII 15% had average values of 2.23%, 1.56%, and 1.15%, respectively. The results of SPSS testing also showed various average values that were significant (p<0.05). From the obtained data, FIII was determined to be the most effective moisturizing formula. Keywords: Papaya leaf, stick heel, moisturizer.